2010
DOI: 10.1143/jjap.49.100206
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystal Addressing by Graphene Electrodes Made from Graphene Oxide

Abstract: The electrooptic characteristics of the field-induced reorientation of a nematic liquid crystal are studied using graphene layers as transparent conductive electrodes. The covering of a large area with highly conductive graphene was achieved by the thermal reduction of a graphene oxide film. The conductivity of the graphene electrode provides electrooptic properties that are comparable to those of liquid crystal cells with two conventional indium tin oxide electrodes. This result confirms earlier studies and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The comparison of the chemical stabilities of graphene and ITO also shows a remarkable advantage for graphene electrodes because ion diffusion easily takes place when ITO serves as the transparent electrode. Recent reports showed that in the case of a 6 nm thick thermally reduced GO film, the performance of prepared LCD device was comparable to that of ITO electrodes 135…”
Section: Applications In Organic Electronicsmentioning
confidence: 91%
“…The comparison of the chemical stabilities of graphene and ITO also shows a remarkable advantage for graphene electrodes because ion diffusion easily takes place when ITO serves as the transparent electrode. Recent reports showed that in the case of a 6 nm thick thermally reduced GO film, the performance of prepared LCD device was comparable to that of ITO electrodes 135…”
Section: Applications In Organic Electronicsmentioning
confidence: 91%
“…It has been found that the electrooptical characteristics of such devices are superior in nature. In a similar fashion GO has been utilized in its reduced form in LC cells to study the field-induced reorientation of a nematic LC [133,134]. These preliminary results are very encouraging for future LC devices.…”
Section: Thermotropic Lcs Of Synthetic Nanographenesmentioning
confidence: 90%
“…A graphene based touch screen can almost handle twin strains compared to conventional devices. Researchers have shown that the performance of prepared LCD using thermally thick GO has better results compared to traditional ITO-based devices [133]. In addition, graphene based LED has better performance compared to the featured ITO-based electrodes.…”
Section: Application Of Graphene In Ledmentioning
confidence: 99%